A new species and new records of spiders (Aranei) in the south of European Russia - A.V. Ponomarev; V.Yu. Shmatko (Кавказский энтомологический бюллетень, 2022)
A new species of spider from the family Gnaphosidae Marinarozelotes ponticus Ponomarev, sp. n. is described from the south of Russia (Krasnodar Region). The new species is close to the Mediterranean species Marinarozelotes bardiae (Caporiacco, 1928), from which it differs in the greater length of the retrolateral loop of the embolar base and the presence of the distal protrusion of the embolus. The holotype is deposited in the Zoological Museum of the Moscow State University (Moscow, Russia), the paratypes are kept in the mentioned institution and in the personal collection of A.V. Ponomarev (Razdorskaya, Rostov Region, Russia). Data on the first records of Callilepis schuszteri (O. Herman, 1879) in Volgograd Region, Heliophanus simplex Simon, 1868 and Synema ornatum (Thorell, 1875) in Rostov Region are given